Carbon dating reveals a seasonal progression in the source of particulate organic carbon exported from the Greenland Ice Sheet. Issue 12 (22nd June 2017) - Kohler, T. J.; Žárský, J. D.; Yde, J. C.; Lamarche‐Gagnon, G.; Hawkings, J. R.; Tedstone, A. J.; Wadham, J. L.; Box, J. E.; Beaton, A. D.; Stibal, M.
Abstract: Surface melt from the Greenland Ice Sheet (GrIS) collects particulate organic carbon (POC) as it drains into subglacial environments and transports it downstream where it serves as a microbial substrate. We hypothesized that older POC is entrained by meltwaters as the subglacial drainage network expands upglacier over the summer. To test this, POC samples were collected from a meltwater river exiting the GrIS over an ablation season and 14 C dated. Resulting values were compared with meltwater hydrochemistry and satellite observations of the catchment area. We found that POC ages increased from ~5000 to ~9000 years B.P. until peak discharge and catchment size. Afterward, significant fluctuations in POC age were observed, interpreted to result from periods of high and low subglacial hydrological pressure and sediment supply and subsequent exhaustion. These observations suggest a seasonal progression in the source of POC exported from the GrIS and provide evidence for a seasonally evolving subglacial drainage system. Key Points: A seasonal progression was observed in 14 C ages of POC exported from beneath the GrIS We propose that patterns result from the seasonal expansion and evolution of the subglacial drainage system Future changes in glacial melt may affect downstream productivity via shifts in the bioavailability of carbon